Natural systems design approach to wastewater management for the enhancement of domestic water sources in Brgy. San Ildefonso, Alaminos, Laguna - Machate, Maria Rose Ann P. (College of Architecture, University of the Philippines Diliman, 2018)
Barangay San Ildefonso is a rural community listed as one of the target beneficiaries of the SALINTUBIG Program by the Department of Interior and Local Government in the year 2016. The criteria considered for ranking target beneficiaries for the program include access level, poverty incidence and incidence of waterborne diseases. Today, despite having most of the households connected to the groundwater supply system, residents are still exposed to risks as their source of water may be contaminated by the untreated domestic wastewater coming from their won households. Through the conduct of interviews, surveys, site observations, map extraction and other data gathering procedures, an alternative solution to wastewater treatment is identified. This study introduces the use of natural systems as an approach to address this problem regarding wastewater treatment. Natural Systems include wetland systems and aquatic or waste stabilization systems that are low- cost and effective alternatives for wastewater treatment. After much analysis of the study site's environmental characteristics, the most appropriate site for the treatment facility was selected. Data results from the survey conducted on the residents and standards on designing the treatment lagoons were considered in the programming and designing phases of the wastewater treatment park. Results from the calculation of the effluent quality after treatment show that although the target effluent quality was, Class D intended mostly for irrigation and water closet flushing, values from the calculation show a Class AA effluent. Note, however, that the values used in computations are the best scenarios indicated in reference manuals, given that the best conditions for the natural treatment to occur is satisfied in the actual environment.